Refinement of Ti-6Al-4V prior-β grain structure in the as-deposited condition via process control during wire-direct energy deposition - Wainwright, James; Williams, Stewart; Ding, Jialuo (Elsevier, 2023)
This study demonstrates that refinement of the prior-β grains generated during the wire-direct energy deposition of Ti‐6Al‐4V is achievable whilst maintaining a stable processing condition in the as-deposited condition, not reliant on penetration of the feedstock to the melt pool. Previous studies on prior-β grain refinement of Ti‐6Al‐4V have been reliant on either post-processing, alloy modification or agitation of the melt pool to achieve refinement. Through process control alone, it was identified that an increase in the deposition rate for a fixed energy input led to a reduction in the specific energy density of deposited material. Utilising pyrometry, it was determined that the reduction in the specific energy density led to a decrease in the thermal gradient, measured using a linear thermal gradient approximation, encouraging apparent homogenous nucleation within the melt pool. Whilst maintaining a stable ‘droplet’ transfer mode, the gradual reduction in specific energy density transformed the grain structure from the typical columnar morphology through a mixed morphology to an equiaxed grain morphology; confirmed via prior-β grain reconstructions and inverse pole figure analysis made possible by electron back scattered diffraction microscopy of the deposited samples. Microhardness measurements demonstrated larger variations in the refined prior-β grain specimens as compared to the columnar as a result of more complex α morphologies generated.
Keywords: Ti-6Al-4V; Additive manufacturing; Grain refinement; Columnar-to-equiaxed transition; As-deposited